Savor it : a novel - DeWitt, Tarah (St. Martin's Paperbacks, 2025)
"Summer won't last forever. Sage Byrd has lived in the coastal town of Spunes, Oregon (not to be confused with Forks, Washington) her entire life. She's learned to love her small world, with the misfit animals on her hobby farm, and her friendships with the town's inhabitants. But when her 5-year relationship ends and her ex, town-golden-boy Ian, suddenly gets engaged, Sage needs a win - something that will convince everyone to stop pitying her all the time, and to put Ian in his place. The Festival of Spunes, the town's annual summer competition, would be the perfect opportunity. She just needs a partner. Fisher Lange was a hotshot chef in New York City until the loss of his sister left him numb, grieving, and responsible for his teenage niece Indy. When Fisher loses his Michelin star along with his love of cooking, his boss sends him and Indy to Spunes on a much-needed summer sabbatical to consult on a restaurant opening. But when clashes with the townspeople threaten his last chance to redeem himself and a kiss with his new neighbor Sage leads to dating rumors, a strategic alliance might just be the best way to turn things around. A deal is struck. Sage will improve Fisher's image in the eyes of the town and remove the roadblocks he is facing with the restaurant, and Fisher will be Sage's partner for the competition. But as their pact quickly turns into steamy rendezvous, emotional wounds begin to heal, and the pair tries to savor every moment, they start to realize that summer is racing by much faster than they would like... Filled with spicy summer fun, small-town charm, and Big Feelings, this highly anticipated romcom is Tarah DeWitt's best yet"--